2, 4‐Dichlorophenoxyacetic‐N‐methylmethanamine and haloxyfop‐P‐methyl interaction: Sequential and interval applications to effectively control sourgrass and fleabane. (30th January 2020) - Leal, Jéssica Ferreira Lourenço; Souza, Amanda dos Santos; Ribeiro, Samia Rayara de Sousa; de Oliveira, Gabriella Francisco Pereira Borges; Araujo, André Lucas Simões; Borella, Junior; Langaro, Ana Claudia; Machado, Aroldo Ferreira Lopes; de Pinho, Camila Ferreira
Abstract: Sourgrass ( Digitaria insularis L.) and fleabane ( Conyza spp. L.) constitute a major challenge to weed management in soybean [ Glycine max  (L.) Merr.] production systems in Brazil, especially when both are resistant to glyphosate and present concurrently. The aim of this study was to evaluate the interaction of haloxyfop‐P‐methyl [methyl(R)‐2{4‐{3‐chloro‐5(trifluoromethyl)‐2‐pyridyloxy] phenoxy} propanoate] and 2, 4‐D [2, 4‐Dichlorophenoxyacetic acid‐N‐methylmethanamine] to control sourgrass at three to four tillers and flowering stages and 12‐ to 15‐cm fleabane at vegetative stage. The experiments were arranged in a randomized complete block design with four replicates and were conducted twice. Treatments were composed of haloxyfop‐P‐methyl and 2, 4‐D applied sequentially at 3‐, 6‐, and 12‐d intervals. Treatments also included an untreated check, haloxyfop‐P‐methyl, and 2, 4‐D sequentially (without interval) and stand‐alone applications of both herbicides. All treatments across experiments completely controlled fleabane plants, except haloxyfop‐P‐methyl alone. Haloxyfop‐P‐methyl applied ≥6 d before 2, 4‐D controlled flowering and three‐ to four‐tiller sourgrass plants at rates of 50 and 100%, respectively. Based on results of this study, haloxyfop‐P‐methyl should be applied ≥6 d before 2, 4‐D in a sequential application structure to control fleabane and sourgrass (three or four tillers) when present concurrently.